Village Baseline Study: Site Analysis Report for Xai Xai, Zongoene Village, Bairro 1, Mozambique - Onyango, Leah; Raimundo Finiasse, A; Mango, Joash; Wamubeyi, B.; Loo, L; Guambe, D; Michaque Manhique, H; Dixon, R. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This is the report of the village baseline study of Zongoene Village, Bairro 1, in the CCAFS benchmark site of Xai Xai, Mozambique in May 2013 to complement an earlier household baseline survey done in the same village. Zongoene village is located by the coast at the mouth of the Limpopo River where there are extensive wetlands along with forests and sand dunes. The village is divided into five sections: Bairro 1, Bairro 2, Bairro 3, Bairro 4 and Bairro 5. Zongoene is the result of a government resettlement program that brought people together to ease service provision. Nonetheless, the level and quality of services remain very low with roads in bad condition, local schools poorly built and lacking water, one hospital with insufficient staff and resources, and nascent electrical availability. The concentrated and expanding population is also increasing pressures on the environment as demand for food and farmland grows.